Customer Satisfaction Assessed from Lifestyle, Promotion, and Quality - Indah Kumalasari; Bambang Mursito (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2021)
Customer Satisfaction in terms of Shopee's Lifestyle, Promotion, and Service Quality. Thesis, Department of Management, Faculty of Economics, Islamic University of Batik Surakarta, 2021. This study aims to prove the simultaneous and partial effect of Customer Satisfaction in terms of Lifestyle, Promotion, and Shopee E-Commerce Service Quality. This research is quantitative descriptive. The population is all Shopee E-commerce buyers. The number of samples used by Sugiyono's guidelines, amounting to 100 respondents, the sample was taken by purposive sampling technique. The data analysis technique used in this study was multiple linear regression analysis. The results of the study indicate that the F-test of lifestyle, promotion, and service quality simultaneously and significantly affects Shopee e-commerce customer satisfaction. The t-test results show that lifestyle has a positive and significant effect on customer satisfaction of Shopee's e-commerce, the promotion has a positive and significant effect on Shopee e-commerce customer satisfaction, service quality has a positive and significant effect on Shopee e-commerce customer satisfaction. The coefficient of determination shows that lifestyle, promotion, and service quality variables on Shopee e-commerce customer satisfaction. The most dominant influence on Shopee e-commerce customer satisfaction is lifestyle variables because it has the largest.